European private international law : commercial litigation in the EU - Calster, Geert van (Oxford : HART, 2024)
"This classic textbook provides a thorough overview of European private international law. It is essential reading for both practitioners and students of private international law and transnational litigation, wherever they may be located: the European rules extend beyond European shores. Opening with foundational questions, the book clearly explains the subject$1 (Bs central tenets: the Brussels I, Rome I and Rome II Regulations (jurisdiction, applicable law for contracts and tort). Additional chapters explore private international law and insolvency, freedom of establishment, and the impact of private international law on corporate social responsibility. The relevant Hague instruments, and the impact of Brexit, are fully integrated in the various chapters. Drawing on the author$1 (Bs rich experience, the new edition retains the book$1 (Bs hallmarks of insight and clarity of expression ensuring it maintains its position as the leading textbook in the field."--s
Keywords: Conflict of laws--European Union countries; International law--European Union countries